Voluntary Exercise-Mediated Protection in TNBS-Induced Rat Colitis: The Involvement of NETosis and Prdx Antioxidants - Nikoletta Almási; Szilvia Török; Amin Al-awar; Médea Veszelka; László Király; Denise Börzsei; Renáta Szabó; Csaba Varga (MDPI AG, 2023)
Inflammatory bowel diseases (IBDs) are autoimmune disorders of the gut. It is increasingly clear that voluntary exercise (VE) may exert protection against IBDs, but the exact background mechanism needs to be elucidated. In the present study, we aimed to investigate the possible role of NETosis and the antioxidant peroxiredoxin (Prdx) enzyme family in VE-induced protection. Wistar Han rats were randomly divided into two groups: sedentary (SED) and VE. After the 6-week voluntary wheel running, animals were treated with 2,4,6-trinitrobenzene sulphonic acid (TNBS) as a model of colitis. Here, we found that VE significantly decreased inflammation and ulceration of the colon in the VE TNBS group compared with SED TNBS. We also found that VE significantly decreased the expression of protein arginine deiminase 4 (PAD4) and myeloperoxidase (MPO), and markedly reduced citrullinated histone H3 (citH3) compared with SED TNBS. Furthermore, VE caused a significant increase in the levels of Prdx6 in the control and TNBS groups. Taken together, we found that a prior 6-week VE effectively reduces inflammation in TNBS-induced colitis, and we suggest that the protective effect of VE may be mediated via the inhibition of NETosis and upregulation of Prdx6 antioxidant.